KANDUNGAN MINERAL ESENSIAL PADA KERANG ALE-ALE (Meretrix sp.) SEGAR DAN TERFERMENTASI (ESSENTIAL MINERALS OF FRESH AND FERMENTED ALE-ALE CLAMS (Meretrix sp.)) - Mega Sari Juane Sofiana; Ikha Safitri; Warsidah Warsidah; Syarif Irwan Nurdiansyah; Anthoni Batahan Aritonang; Shifa Helena; Kurniawan Alam Muza’ki (Tanjungpura University, 2020)
Ale-ale are popular clams in the coastal area of Ketapang. The local community uses the clams as food, one of which is in the form of fermented products. In the fermentation process, the nutritional content of course will be different from fresh ale-ale because it has gone through the preservation process. One of the goals of processing it into fermented products is to increase the product's durability. Essential mineral contents (Fe, Mn, Zn) in fermented products is different and tends to decrease. Essential mineral testing used the Atomic Absorption Spectroscopy (AAS) method. The water content and ash content of fresh ale-ale were 63.1% and 15.8%, respectively. While the water content and ash content of the fermented ale-ale were 68.69% and 17.2%, respectively. The essential mineral contents of fresh ale-ale obtained Fe 23 mg/kg, Zn 1.70 mg/kg and Mn 0.138 mg/kg. In fermented ale-ale, the content of Fe is 9.76 mg/kg, Zn is 0.740 mg/kg and Mn is 0.387 mg/kg.